Comparison of Maqasid al-Shari’ah asy-Syathibi and ibn ‘Ashur perspective of Usul al-Fiqh four mazhab - Alfa Syahriar; Zahrotun Nafisah (Sultang Agung Islamic University, 2020)
Islamic law is established to ensure that human interests related to basic rights inherent in their lives include: the right to life, descent, wealth, thought and respect, can be realized. According to the reality, the problems that arise related to these rights are very complex and sustainable. This consideration necessitates efforts to realize Islamic humanist law in the interests of human life. In Usul Fiqh there is the concept of maslahat, as a standard of how basic human rights can be ensured of their fullness and sustainability. And the theory of Maqashid al-Sharia is seen as quite effective in realizing benefit, which means it is a necessity to study the thoughts of al-Shathibi and Ibn Ashur, because both are seen as very influential figures in the development of Maqashid al-Sharia. Therefore, this study is intended to study in a qualitative-comparative way of thinking of the two figures using the Maqashid al-Sharia framework according to the Ulama of Ushul Fiqh of the Four Mazhab. The results of this study can be stated that the orientation of the theory of Maqashid al-Sharia according to al-Shathibi to realize the benefit of the world and the hereafter, while Ibn Ashur limits only the world. Furthermore, the theory of Maqashid al-Sharia al-Shathibi and Ibn Ashur in the review of Usul Fiqh of Four Mazhab can be stated still in the context permitted by Islamic Sharia.